Professionalism perception and client satisfaction. An analysis of the bouncers-doormen performance - Silva, R.; Amado, A.; Dias, Á. (International Journal of Service Science, Management, Engineering, and Technology, 2022)
This research aims to evaluate the degree of customer satisfaction of the nightclubs with the security guards, as well as the perception of their professionalism in performing their duties. Using survey data from 479 nightclubs clients to assess the clients’ professionalism perception of the bouncers-doormen and satisfaction. The results indicate an overall satisfaction and bouncers-doormen to be recognized as professionals. Findings also partially contradict previous research. Despite recognizing a certain degree of abuse of power, customers consider those professional as helpful, especially in emergency situations where they provide guidance and the necessary support. They are also considered to properly watch and protect people and goods in night-time entertainment spaces and have good ability to foresee and anticipate incidents.